Synthesis of vancomycin functionalized fluorescent gold nanoparticles and selective sensing of mercury (II) - Tiwari, Atul Kumar; Yadav, Hari Prakash; Gupta, Munesh Kumar; Narayan, Roger J.; Pandey, Prem C. (Frontiers in Chemistry, 2023)
Mercury ions (Hg2+) are widely found in the environment; it is considered a major pollutant. Therefore, the rapid and reliable detection of Hg2+ is of great technical interest. In this study, a highly fluorescent, sensitive, and selective fluorometric assay for detecting Hg2+ ions was developed using vancomycin functionalized and polyethyleneimine stabilized gold nanoparticles (PEI-f-AuNPs@Van). The as-made gold nanoparticles were highly fluorescent, with excitation and emission maxima occurring at 320 and 418 nm, respectively. The size of nanoparticles was 7 nm; a zeta potential of 38.8 mV was determined. The XRD analysis confirmed that the nanoparticles possessed crystalline structure with face centerd cubic symmetry. Using the PEI-f-AuNP@Van probe, the detection limit of Hg2+ ion was achieved up to 0.988 nM (within a linear range) by calculating the KSV. However, the detection limit in a natural environmental sample was shown to be 12.5 nM. Furthermore, the selectivity tests confirmed that the designed probe was highly selective to mercury (II) cations among tested other divalent cations. Owing to its sensitivity and selectivity, this approach for Hg2+ ions detection can be utilized for the analysis of real water samples.